(untitled) (Research, Society and Development, 2022)
Cosmetic dentistry has gained a lot of prominence among the population, in which the smile is a fundamental part of self-esteem and also improves the patient’s quality of life. Studies define normal gingival exposure at up to 2 mm, being considered a gingival smile greater than that. Botulinum toxin is one of the forms of treatment, which can be exclusive or associated with other treatments depending on the need of each one. The present study aimed to carry out a literature review on the association of botulinum toxin type A for the correction of gummy smile, with articles from 2011 to 2021 in the National Library of Medicine (PubMed), Google Scholar and Scientific Electronic Library Online databases (SciELO). The articles found report the effectiveness of the treatment of gummy smile with the use of botulinum toxin, botox, in the performance of hyperactivity of the lip muscles, in addition to having a low risk of complication, it has satisfactory results, but with disadvantages regarding the cost and duration of the treatment. toxin activity. However, it is evident that it is a safe and effective procedure for the treatment of gummy smile, requiring further studies on the conduct.